Prestressed concrete bridges design and construction - Hewson, Nigel R. (Thomas Telford, 2003)
Concrete is the most common material for bridge construction around the world, and prestressed concrete is frequently the material of choice. Extensively illustrated throughout, this book covers all aspects of designing prestressed concrete bridge decks.